Values, Partisan Interest, and the Voting Age: Lessons from Australia. Issue 5 (2nd July 2021) - Miragliotta, Narelle; Murray, Sarah; Drum, Martin
Abstract : The decline in youth participation in elections has been an ongoing concern in Australia, in spite of the requirement for compulsory turnout. In 2018, and in response to these concerns, the Australian p arliament debated an electoral amendment that would lower the national voting age to 16 years. The Bill, however, did not succeed even though two opposition parties—the Australian Labor Party and the Australian Greens—supported the reform and the Morrison G overnment accepted the premise that youth electoral disengagement was a troubling phenomenon. Drawing on veto player theory, this article examines how the legislative dynamics intersected with partisan self‐interest and party value priorities to undercut the case for lowering the voting age to 16. The Australian case highlights the ways in which latent ideological differences among parties can serve to divide them on the inclusiveness of franchise, and the democratic goals to be served by voting. Related Articles: Cormack, Lindsey. 2019. "Leveraging Peer‐to‐Peer Connections to Increase Voter Participation in Local Elections." Politics & Policy 47 (2): 248‐266. https://doi.org/10.1111/polp.12297 Fisher, Patrick. 2020. "Generational Replacement and the Impending Transformation of the American Electorate." Politics & Policy 48 (1): 38‐68. https://doi.org/10.1111/polp.12340 Ike, Vivian. 2020. "The Impact of Veto Players on Incremental and Drastic Policy Making: Australia's Carbon tax Policy and its Repeal." Politics & Policy 48 (2): 232‐264. https://doi.org/10.1111/polp.12346 Abstract : Valores, interés partidista y la edad de votar: lecciones de Australia: La disminución de la participación de los jóvenes en las elecciones ha sido una preocupación constante en Australia, a pesar del requisito de participación obligatoria. En 2018, y en respuesta a estas preocupaciones, el parlamento australiano debatió una enmienda electoral que reduciría la edad nacional para votar a 16 años. Sin embargo, el proyecto de ley no tuvo éxito a pesar de que dos partidos de la oposición, el Partido Laborista Australiano y los Verdes australianos, apoyaron la reforma y el Gobierno de Morrison aceptó la premisa de que la desconexión electoral de los jóvenes era un fenómeno preocupante. Sobre la base de la teoría del jugador con veto, este artículo examina cómo la dinámica legislativa se cruzó con el interés propio de los partidos y las prioridades de valor del partido para socavar el caso de reducir la edad para votar a 16 años. El caso australiano destaca la existencia de diferencias ideológicas que dividen a los partidos en el sufragio y las diferentes concepciones de los objetivos democráticos que se alcanzarán mediante la votación. Abstract : 价值、党派利益和投票年龄：从澳大利大得出的经验: 尽管存在强制参与选举的要求，但青年人选举参与率下降一直是澳大利亚的一个持续关切。2018年，为响应该关切，澳大利亚议会就一项将全国投票年龄降低至16岁的选举修订案进行辩论。不过，该法案并未取得成功，尽管两个反对党—澳大利亚工党和绿党—支持改革，并且莫里森政府接受"青年人不参与选举是一个麻烦现象"这一假设。基于否决者理论，本文分析了立法动态如何与党派自身利益及党派价值重点相交叉，以削弱将投票年龄降至16岁这一情况的效果。澳洲案例强调了意识形态差异的存在，这种差异通过选举权和由投票完成的不同民主目标概念来区分各党。